Concurrent suppression of hyperlipidemia and intestinal polyp formation by NO-1886, increasing lipoprotein lipase activity in Min mice - Niho, Naoko (National Academy of Sciences, 2005)
We have previously reported a hyperlipidemic state in two strains of Apc-deficient mice, Min and Apc(1309), associated with low expression levels of lipoprotein lipase (LPL) in the liver and small intestine, and enforced induction of LPL mRNA by peroxisome proliferator-activated receptor (PPAR)α and PPARγ agonists clearly suppressed hyperlipidemia and intestinal polyp formation in these mice. Meanwhile, a compound, NO-1886, has been shown to increase LPL mRNA and protein levels but not to possess PPARα and PPARγ agonistic activity. In this study, therefore, the effects of NO-1886 on hyperlipidemia and intestinal polyp formation were investigated in Min mice. Administration of 400 and 800 ppm NO-1886 in the diet for 13 weeks from 7 weeks of age caused a reduction of serum triglycerides to 39% and 31% of the untreated value, respectively, and the values for very low-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol were improved almost to the wild-type level with a corresponding elevation of the LPL mRNA. Moreover, total numbers of intestinal polyps in the groups receiving NO-1886 at 400 and 800 ppm were decreased to 48% and 42% of the control value, respectively. We also found that NO-1886 suppressed cyclooxygenase-2 transcriptional promoter activity in a reporter gene assay and reduced cyclooxygenase-2 mRNA levels in the small intestine of Min mice. These results indicate that suppression of serum lipid levels by increasing LPL activity may contribute to a reduction of intestinal polyp formation with Apc-deficiency, and NO-1886 and its derivatives could be useful as chemopreventive agents for colon cancer.